(untitled) (Ciencia Veterinaria, 2017)
In arid and semi-arid regions, it is generally not possible to keep farms supported exclusively on natural pasture due to the low supply of forage, poor media quality and large output fluctuations between years. In order to achieve economic production levels in periods of drought, the silage is necessary to supplement the feeding of cattle, sheep and goats with canned foods, including. This technique, by its shape and size storage has the disadvantage not be marketed, transported to places of consumption and processed in small scale. This project preparation technology applied in a manner that its size allows the transfer, handling and disposal without altering their quality